Carbon Nanotubes Paste Electrodes as new Detectors for Capillary Electrophoresis - Chicharro, Manuel (2005)
Carbon nanotubes paste electrodes (CNTPE) prepared with short (1–5 μm length) and long carbon nanotubes (5–20 μm length) of 20–50 nm diameter have demonstrated to be highly useful as detectors in flow injection analysis and capillary electrophoresis. Compared to the classical graphite paste electrode, CNTPE improved the detection limits of dopac, ascorbic acid, dopamine, norepinephrine and epinephrine. The content of agglutinant has shown to be an important variable in the preparation of these carbon nanotubes composites. Even when no substantial differences were observed between the electrodes, those prepared with long carbon nanotubes (55.0%, w/w) and mineral oil (45.0%, w/w) have allowed us to obtain less noisy and more reproducible signals. In this article we also report the successful use of a new electrochemical cell for the detection in capillary electrophoresis that allows an easier handling and more reproducible responses. Therefore, the combination of the carbon nanotubes electrocatalytic activity with the known advantages of composite materials, the efficiency of the new electrochemical cell and the excellent separative properties of capillary electrophoresis represents a very important alternative for new electroanalytical challenges.